Hardmetal and cutting tools

The carbide alloy, characterized by a high volume percentage of tungsten carbide particles and a cobalt-rich bonding phase with specific crystal structure composition, addresses the challenge of reduced tool life in cutting tools, especially when machining high-strength materials, by enhancing deformation resistance and tool longevity.

JP7666744B1Active Publication Date: 2025-04-22SUMITOMO ELECTRIC INDUSTRIES LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024529595
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-09-26
Publication Date
2025-04-22
Estimated Expiration
2043-09-26

AI Technical Summary

Technical Problem

Cutting tools face increased difficulty in cutting advanced materials, leading to reduced tool life and efficiency, especially when intermittently machining high-strength materials.

Method used

A carbide alloy comprising a high volume percentage of tungsten carbide particles and a bonding phase with a cobalt content of 80% or more, where the bonding phase in the internal region has a specific crystal structure composition that enhances deformation resistance.

Benefits of technology

The carbide alloy extends the tool life of cutting tools, particularly when used for intermittent machining of high-strength materials, by improving wear resistance and fracture resistance through enhanced bonding phase properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007666744000005
    Figure 0007666744000005
  • Figure 0007666744000006
    Figure 0007666744000006
  • Figure 0007666744000001
    Figure 0007666744000001
Patent Text Reader

Abstract

A cemented carbide comprising a plurality of tungsten carbide particles and a binder phase, the cemented carbide containing 89 volume % or more of the tungsten carbide particles and the binder phase in total, the cemented carbide containing 1.8 volume % or more and 20 volume % or less of the binder phase, the binder phase containing 80 mass % or more of cobalt, the cemented carbide containing an inner region at a distance of 300 μm or more from a surface, and an area S of cobalt having a hcp structure in the binder phase of the inner region (hcp) and the area S of cobalt with fcc structure (fcc) The sum of the above areas S (hcp) Percentage of {S (hcp) / (S (hcp) +S (fcc) )}×100 is a cemented carbide alloy having a hardness of 45% or more.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to hardmetals and cutting tools. [Background technology]

[0002] Conventionally, cemented carbide having a plurality of tungsten carbide particles and a binder phase has been used as a material for cutting tools (Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2004-131769 A Summary of the Invention

[0004] The cemented carbide of the present disclosure is A cemented carbide comprising a plurality of tungsten carbide particles and a binder phase, The cemented carbide contains 89% by volume or more of the tungsten carbide particles and the binder phase in total, The cemented carbide contains 1.8% by volume or more and 20% by volume or less of the binder phase, The binder phase contains 80% by mass or more of cobalt, The cemented carbide includes an internal region having a distance from the surface of 300 μm or more; In the binder phase of the internal region, the area S of cobalt having a hcp structure (hcp) and the area S of cobalt with fcc structure (fcc) The sum of the above areas S (hcp) Percentage of {S (hcp) / (S (hcp) +S (fcc) )}×100 is a cemented carbide alloy having a hardness of 45% or more. [Brief description of the drawings]

[0005] [Figure 1] FIG. 1 is a schematic cross-sectional view of a cemented carbide according to a first embodiment. [Diagram 2] FIG. 2 is a schematic diagram of a cutting tool according to the second embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0006] [Problem that this disclosure aims to solve] In recent years, work materials have become increasingly difficult to cut in cutting processes, and the conditions under which cutting tools are used have become harsher. For this reason, there is a demand for improved properties in the cemented carbide alloys used as the base material for cutting tools. In particular, there is a demand for cemented carbide alloys and cutting tools equipped with them that enable the tool to have a longer life, even when used as materials for cutting tools for interrupted cutting of high-strength materials.

[0007] [Effects of this disclosure] According to the present disclosure, it is possible to provide a cemented carbide that enables a longer tool life, particularly when used as a material for cutting tools for intermittent machining of high-strength materials, and a cutting tool including the same.

[0008] [Description of the embodiments of the present disclosure] First, the embodiments of the present disclosure will be listed and described. (1) The cemented carbide disclosed herein is A cemented carbide comprising a plurality of tungsten carbide particles and a binder phase, The cemented carbide contains 89% by volume or more of the tungsten carbide particles and the binder phase in total, The cemented carbide contains 1.8% by volume or more and 20% by volume or less of the binder phase, The binder phase contains 80% by mass or more of cobalt, The cemented carbide includes an internal region having a distance from the surface of 300 μm or more; In the binder phase of the internal region, the area S of cobalt having a hcp structure (hcp) and the area S of cobalt with fcc structure (fcc) The sum of the above areas S (hcp) Percentage of {S (hcp) / (S (hcp) +S (fcc) )}×100 is a cemented carbide alloy having a hardness of 45% or more.

[0009] According to the present disclosure, it is possible to provide a cemented carbide that enables a longer tool life, particularly when used as a material for cutting tools for intermittent machining of high-strength materials, and a cutting tool including the same.

[0010] (2) In the above (1), the percentage {S (hcp) / (S (hcp) +S (fcc) )}×100 may be 50% or more and 70% or less. This improves the deformation resistance of the binder phase, and a cutting tool including the cemented carbide can have a longer tool life.

[0011] (3) In the above (1) or (2), the binder phase may further contain at least one first element selected from the group consisting of silicon, phosphorus, germanium, tin, rhenium, ruthenium, osmium, iridium, and platinum, which improves the deformation resistance of the binder phase and allows a cutting tool including the cemented carbide to have a longer tool life.

[0012] (4) In the above (3), the percentage of the mass M1 of the first element to the sum M1+M2 of the mass M1 of the first element and the mass M2 of cobalt, {M1 / (M1+M2)}×100, may be 1% or more and 6% or less. According to this, the binder phase can have both superior hardness and superior toughness, so that a cutting tool including a cemented carbide containing the binder phase can have a longer tool life.

[0013] (5) A cutting tool according to the present disclosure is a cutting tool having a cutting edge made of the cemented carbide according to any one of (1) to (4) above.

[0014] According to the present disclosure, it is possible to provide a cutting tool having a long tool life, especially when used for interrupted cutting of high strength materials.

[0015] [Details of the embodiment of the present disclosure] Specific examples of the cemented carbide and cutting tool of the present disclosure will be described below with reference to the drawings. In the drawings of the present disclosure, the same reference numerals represent the same or corresponding parts. Furthermore, dimensional relationships such as length, width, thickness, and depth have been appropriately changed for clarity and simplification of the drawings, and do not necessarily represent actual dimensional relationships.

[0016] In this disclosure, an expression in the form "A to B" means the upper and lower limits of a range (i.e., A or more and B or less). When no unit is specified for A and a unit is specified only for B, the unit of A and the unit of B are the same.

[0017] In the present disclosure, when a compound or the like is represented by a chemical formula, unless the atomic ratio is particularly limited, it is intended to include any conventionally known atomic ratio, and should not necessarily be limited to only those within the stoichiometric range.

[0018] In the present disclosure, when one or more numerical values ​​are described as the lower limit and the upper limit of a numerical range, a combination of any one numerical value described as the lower limit and any one numerical value described as the upper limit is also disclosed. For example, when a1 or more, b1 or more, and c1 or more are described as the lower limit, and a2 or less, b2 or less, and c2 or less are described as the upper limit, a1 or more and a2 or less, a1 or more and b2 or less, a1 or more and c2 or less, b1 or more and a2 or less, b1 or more and b2 or less, b1 or more and c2 or less, c1 or more and a2 or less, c1 or more and b2 or less, and c1 or more and c2 or less are disclosed.

[0019] [Embodiment 1: Carbide] A cemented carbide according to one embodiment of the present disclosure will be described with reference to FIG. The cemented carbide 3 according to one embodiment of the present disclosure (hereinafter also referred to as "embodiment 1") is A cemented carbide (3) comprising a plurality of tungsten carbide particles (1) and a binder phase (2), The cemented carbide 3 contains tungsten carbide particles 1 and a binder phase 2 in a total amount of 89 volume % or more, The cemented carbide 3 contains a binder phase 2 in an amount of 1.8 volume % or more and 20 volume % or less, The binder phase 2 contains 80% by mass or more of cobalt, The cemented carbide 3 includes an internal region that is 300 μm or more away from the surface, In the inner region of the binder phase, the area of ​​cobalt having the hcp structure S (hcp) and the area S of cobalt with fcc structure (fcc) The total area S (hcp) Percentage of {S (hcp) / (S (hcp) +S (fcc) )}×100 is 45% or more, and is cemented carbide 3.

[0020] The cemented carbide of the first embodiment can provide a cemented carbide that enables a tool to have a long service life, even when used as a material for cutting tools for interrupted cutting of high-strength materials, and a cutting tool including the same. The reason for this is not clear, but is presumed to be as follows.

[0021] The cemented carbide of the first embodiment comprises a plurality of tungsten carbide particles (hereinafter also referred to as "WC particles") and a binder phase, and the total content of the WC particles and the binder phase in the cemented carbide is 89 volume % or more. As a result, the cemented carbide has high hardness and strength, and a cutting tool comprising the cemented carbide can have excellent wear resistance and chipping resistance.

[0022] The cemented carbide of the first embodiment contains a binder phase of 1.8% by volume or more and 20% by volume or less, and the binder phase contains 80% by mass or more of cobalt. Thus, the cemented carbide has high hardness and strength, and a cutting tool including the cemented carbide can have excellent wear resistance and chipping resistance.

[0023] In the binder phase of the internal region of the cemented carbide of embodiment 1, the area S of cobalt having an hcp structure (hcp) and the area S of cobalt with fcc structure (fcc) The total area S (hcp) Percentage of {S (hcp) / (S (hcp) +S (fcc))}×100 is 45% or more. This improves the deformation resistance of the binder phase, and improves the deformation resistance of the cemented carbide.

[0024] <Composition of cemented carbide> The cemented carbide of the first embodiment contains tungsten carbide particles and a binder phase in a total amount of 89% or more by volume. This can increase the hardness of the cemented carbide. The cemented carbide may contain tungsten carbide particles and a binder phase in a total amount of 89% to 100% by volume, 90% to 100% by volume, 91% to 100% by volume, or 92% to 100% by volume.

[0025] The cemented carbide of the first embodiment contains 1.8% by volume or more and 20% by volume or less of a binder phase. This can increase the hardness and toughness of the cemented carbide. The content of the binder phase in the cemented carbide may be 2.0% by volume or more and 19.0% by volume or less, 3.0% by volume or more and 18.0% by volume or less, or 4.0% by volume or more and 17.0% by volume or less.

[0026] The cemented carbide of the first embodiment may be composed of a plurality of tungsten carbide particles and a binder phase. In this case, the cemented carbide may contain impurities within a range that does not impair the effects of the present disclosure.

[0027] The cemented carbide may contain other phases (not shown) in addition to the tungsten carbide particles and binder phase. The other phases may include carbides, nitrides, or carbonitrides containing at least one element selected from the group consisting of titanium (Ti), tantalum (Ta), niobium (Nb), zirconium (Zr), hafnium (Hf), and molybdenum (Mo). The composition of the other phases may be, for example, at least one selected from the group consisting of TiCN, TaC, NbC, ZrC, HfC, Cr3C2, and Mo2C.

[0028] The cemented carbide of the first embodiment may be composed of tungsten carbide particles, a binder phase, and other phases. In this case, the cemented carbide may contain impurities as long as the effects of the present disclosure are not impaired.

[0029] The content of other phases in the cemented carbide is permitted within a range that does not impair the effects of the present disclosure. For example, the content of other phases in the cemented carbide may be 0 vol% or more and 11 vol% or less, more than 0 vol% and 11 vol% or less, more than 0 vol% and 7 vol% or less, or more than 0 vol% and 4 vol% or less.

[0030] The cemented carbide of the first embodiment may contain impurities. Examples of impurities include iron (Fe), calcium (Ca), silicon (Si), and sulfur (S). The content of impurities in the cemented carbide is permissible within a range that does not impair the effects of the present disclosure. For example, the content of impurities in the cemented carbide may be 0% by mass or more and less than 0.1% by mass. The content of impurities in the cemented carbide is measured by ICP optical emission spectroscopy (Inductively Coupled Plasma Emission Spectroscopy). The measurement device that can be used is Shimadzu Corporation's "ICPS-8100" (trademark).

[0031] The content of tungsten carbide particles in the cemented carbide of embodiment 1 may be 67 vol. % to 98.2 vol. %, 70 vol. % to 97 vol. %, or 75 vol. % to 96 vol. %.

[0032] The method for measuring the content (volume %) of tungsten carbide particles in the cemented carbide and the content (volume %) of the binder phase in the cemented carbide is as follows.

[0033] (A1) An arbitrary position of the cemented carbide is cut out to expose a cross section, which is then mirror-finished using a cross-section polisher (manufactured by JEOL Ltd.).

[0034] (B1) The mirror-finished surface of the cemented carbide is analyzed using an energy dispersive X-ray spectrometer (SEM-EDX) attached to a scanning electron microscope (equipment: Carl Zeiss "Gemini450" (trademark)) to identify the elements contained in the cemented carbide.

[0035] (C1) The mirror-finished surface of the cemented carbide is photographed with a scanning electron microscope (SEM) to obtain a backscattered electron image. The photographed area is set to the center of the cemented carbide cross section, that is, a position that does not include areas with properties that are clearly different from the bulk part, such as the surface area of ​​the cemented carbide (a position where the entire imaged area is the bulk part of the cemented carbide). The observation magnification is 5000x. The measurement conditions are an acceleration voltage of 3kV, a current value of 2nA, and a working distance (WD) of 5mm.

[0036] (D1) The photographed region of (C1) above is analyzed using SEM-EDX to identify the distribution of the elements identified in (B1) above in the photographed region, and an element mapping image is obtained.

[0037] (E1) The backscattered electron image obtained in (C1) above is imported into a computer and binarized using image analysis software (OpenCV, SciPy). In the binarized image, tungsten carbide particles are shown in white, and the bond phase is shown in gray to black. Note that the binarization threshold changes depending on the contrast, so it is set for each image.

[0038] (F1) By superimposing the element mapping image obtained in (D1) above and the image after the binarization process obtained in (E1) above, the respective regions of the tungsten carbide particles and the binder phase are identified on the image after the binarization process. Specifically, the regions shown in white in the image after the binarization process and in which tungsten (W) and carbon (C) exist in the element mapping image correspond to the regions of the tungsten carbide particles. The regions shown in gray to black in the image after the binarization process and in which cobalt (Co) exists in the element mapping image correspond to the regions of the binder phase.

[0039] (G1) A rectangular measurement field of view of 24.9 μm × 18.8 μm is set in the image after the binarization process. Using the image analysis software, the area percentages of the tungsten carbide particles and the binder phase are measured with the area of ​​the entire measurement field as the denominator.

[0040] (H1) The measurement of (G1) above is carried out in five different non-overlapping measurement fields. In the present disclosure, the average of the area percentages of tungsten carbide particles in the five measurement fields corresponds to the content (volume %) of tungsten carbide particles in the cemented carbide, and the average of the area percentages of the binder phase in the five measurement fields corresponds to the content (volume %) of the binder phase in the cemented carbide.

[0041] If the cemented carbide contains other phases in addition to the WC particles and the binder phase, the content of the other phases in the cemented carbide can be obtained by subtracting the content (volume %) of the tungsten carbide particles and the content (volume %) of the binder phase measured by the above procedure from the total cemented carbide (100 volume %).

[0042] As long as the measurements are performed on the same sample, it has been confirmed that there is almost no variation in the measurement results even if the cut-out location of the cross section of the cemented carbide, the photographing area described in (C1) above, and the measurement field of view described in (G1) above are arbitrarily set and the tungsten carbide particle content and binder phase content of the cemented carbide are measured multiple times according to the above procedure.

[0043] The cemented carbide of embodiment 1 may contain 1% or more by mass of cobalt. The cobalt content of the cemented carbide may be 1.0% or more and 20% or less by mass, 2.0% or more and 15% or less by mass, or 3.0% or more and 12% or less by mass.

[0044] The method for measuring the cobalt content of the cemented carbide is as follows. Analysis is performed using SEM-EDX in the same manner as (A1) to (D1) of the method for measuring the tungsten carbide particle content and the binder phase content of the cemented carbide to obtain an element mapping image. Based on the element mapping image, the cobalt region in the cemented carbide is identified, and the cobalt content is measured. The measurement is performed in five different non-overlapping imaging regions. In the present disclosure, the average of the cobalt contents in the five imaging regions corresponds to the cobalt content of the cemented carbide.

[0045] As long as the measurements were performed on the same sample, it was confirmed that there was almost no variation in the measurement results even if the cut-out location of the cross section of the cemented carbide and the photographing area described in (C1) above were arbitrarily set and the cobalt content of the cemented carbide was measured multiple times according to the above procedure.

[0046] <Tungsten carbide particles> In the cemented carbide of the first embodiment, the tungsten carbide particles include at least one of "pure WC particles (including WC containing no impurity elements and WC containing impurity elements below the detection limit)" and "WC particles containing impurity elements intentionally or unavoidably, as long as the effect of the present disclosure is not impaired." The content of impurities in the tungsten carbide particles (when two or more elements are included as impurities, the total concentration of the elements) is less than 0.1% by mass. The content of impurities in the tungsten carbide particles is measured by ICP emission spectrometry.

[0047] In the first embodiment, the average particle size of the tungsten carbide particles is not particularly limited. The average particle size of the tungsten carbide particles can be, for example, 0.1 μm or more and 3.5 μm or less. It has been confirmed that the cemented carbide of the first embodiment can extend the life of a cutting tool when used as a material for the cutting tool, regardless of the average particle size of the tungsten carbide particles.

[0048] <Binded phase> In the cemented carbide of embodiment 1, the binder phase contains 80% by mass or more of cobalt. This allows the cemented carbide to have excellent toughness. The cobalt content of the binder phase may be 80% by mass or more and 100% by mass or less, 80% by mass or more and less than 100% by mass, or 90% by mass or more and less than 100% by mass.

[0049] The method for measuring the cobalt content of the binder phase is as follows. An element mapping image and an image after binarization are obtained by the same method as (A1) to (E1) of the method for measuring the content of tungsten carbide particles and the content of the binder phase of the cemented carbide. The element mapping image and the image after binarization are superimposed to identify the region in which the binder phase exists in the element mapping image. A rectangular measurement field of view of 24.9 μm×18.8 μm is set in the element mapping image. The cobalt content is measured in the region in which the binder phase exists in the measurement field of view. The above measurement is performed in five different measurement fields that do not overlap each other. In the present disclosure, the average of the cobalt contents in the regions in which the binder phase exists in the five measurement fields of view corresponds to the cobalt content of the binder phase.

[0050] As long as the measurements are performed on the same sample, it has been confirmed that there is almost no variation in the measurement results even if the cut-out location of the cross section of the cemented carbide, the photographing area described in (C1) above, and the measurement field of view described above are arbitrarily set and the cobalt content of the binder phase is measured multiple times according to the above procedure.

[0051] In the cemented carbide of embodiment 1, the binder phase may further contain at least one first element selected from the group consisting of silicon, phosphorus, germanium, tin, rhenium, ruthenium, osmium, iridium, and platinum, which improves the deformation resistance of the binder phase.

[0052] The inclusion of the first element in the binder phase is confirmed by the following procedure. An element mapping image and a binarized image are obtained by the same methods as (A1) to (E1) of the above-mentioned method for measuring the tungsten carbide particle content and binder phase content of a cemented carbide alloy. The element mapping image and the binarized image are superimposed to identify the region in the element mapping image where the binder phase exists. Element Mapping image When the first element is present in the region where the binder phase is present, it is confirmed that the binder phase contains the first element.

[0053] In the binder phase of the cemented carbide of the first embodiment, the percentage {M1 / (M1+M2)}×100 of the mass M1 of the first element with respect to the sum M1+M2 of the mass M1 of the first element and the mass M2 of cobalt may be 1% or more and 6% or less. Here, the units of M1 and M2 are the same. As a result, the binder phase can have both better hardness and better toughness, so that a cutting tool including a cemented carbide including the binder phase can have a longer tool life. Here, the mass M1 of the first element means the total mass of all the types of the first elements when the binder phase includes two or more types of the first elements. The percentage {M1 / (M1+M2)}×100 may be 2% or more and 5% or less, or 3% or more and 4% or less.

[0054] The method for measuring the percentage {M1 / (M1+M2)}×100 is as follows. An element mapping image and a binarized image are obtained by the same method as (A1) to (E1) of the method for measuring the content of tungsten carbide particles and the content of the binder phase of the cemented carbide. The element mapping image and the binarized image are superimposed to identify the region in which the binder phase exists in the element mapping image. A rectangular measurement field of view of 24.9 μm×18.8 μm is set in the element mapping image. In the region in which the binder phase exists in the measurement field of view, the percentage {m1 / (m1+m2)}×100 of the mass m1 of the first element relative to the sum m1+m2 of the mass m1 of the first element and the mass m2 of cobalt is calculated. The above measurement is performed in five different measurement fields of view that do not overlap each other. In the present disclosure, the average of the percentage {m1 / (m1+m2)}×100 in the five measurement fields corresponds to the "percentage {M1 / (M1+M2)}×100" in the binder phase of the cemented carbide.

[0055] As long as measurements were taken on the same sample, it was confirmed that there was almost no variation in the measurement results, even if the cut-out location of the cross section of the cemented carbide, the photographing area described in (C1) above, and the measurement field of view were arbitrarily set, and the percentage {M1 / (M1+M2)}×100 was measured multiple times according to the above procedure.

[0056] In the cemented carbide of the first embodiment, the binder phase may contain, in addition to cobalt and the first element, at least one second element selected from the group consisting of iron, nickel, and chromium. The binder phase may consist of cobalt, the first element, and the second element. The binder phase may consist of cobalt, the first element, the second element, and inevitable impurities. Examples of the inevitable impurities include iron, nickel, and sulfur.

[0057] <Percentage of the binder phase in the inner region {S (hcp) / (S (hcp) +S (fcc) )}×100> The cemented carbide of the first embodiment includes an internal region having a distance of 300 μm or more from the surface, and the area S of cobalt having an hcp (hexagonal close-packed) structure in the binder phase of the internal region (hcp) and the area S of cobalt with fcc (face-centered cubic) structure (fcc) The total area S (hcp) Percentage of {S (hcp) / (S (hcp) +S (fcc) )}×100 is 45% or more. (hcp) / (S (hcp) +S (fcc) )}×100 may be 45% or more and 80% or less, or 50% or more and 70% or less.

[0058] In the present disclosure, the percentage {S (hcp) / (S (hcp) +S (fcc) )}×100 is measured by the following procedure.

[0059] (A2) The cemented carbide is cut along the normal line of its main surface to expose a cross section. If the surface of the cemented carbide does not have a flat area, the cemented carbide is cut from an arbitrary point on the surface in a direction toward the center of gravity of the cemented carbide to expose a cross section. The cross section is mirror-finished using a cross section polisher (manufactured by JEOL Ltd.).

[0060] (B2) The mirror-finished surface of the cemented carbide is observed using a scanning electron microscope (SEM: Carl Zeiss "Gemini450" (trademark)) equipped with an electron backscatter diffraction (EBSD (Electron Backscatter Diffraction Pattern) device: Oxford "Symmetry" (trademark). EBSD analysis is performed on the obtained observation image. The observation image is acquired so as to include an internal region that is 300 μm or more away from the surface of the cemented carbide. A rectangular measurement field of view of 11.5 μm × 8.5 μm is set in the internal region of the observation image. The observation magnification is 10,000 times. The measurement conditions are an acceleration voltage of 15 kV, a current value of 20 nA, 0.02 μm / step, an exposure time of 1.5 to 3 ms, and a measurement time of 10 to 20 minutes.

[0061] (C2) The EBSD analysis results are analyzed using commercially available software (Oxford "AZtecCrystal" (trademark)), the crystal structure of cobalt contained in the binder phase is identified in the above measurement field of view, and a color map is obtained. The crystal structure of cobalt identified here is the crystal structure observed when the cobalt appearing on the mirror-finished surface of the cemented carbide is viewed in plan from the normal direction of the mirror-finished surface.

[0062] (D2) Using the above software, the area S of cobalt having the hcp structure in the bonded phase in the measurement field of view is calculated. (hcp) and the area S of cobalt with fcc structure (fcc) The total area S (hcp) Percentage of {S (hcp) / (S (hcp) +S (fcc) )}×100 is measured. For example, based on the color map, an image A showing tungsten carbide particles in white and cobalt having an hcp structure in black, and an image B showing tungsten carbide particles in white and cobalt having an fcc structure in black are output, and the percentage {S (hcp) / (S (hcp) +S (fcc) )}×100 can be measured.

[0063] (E2) The above percentage {S (hcp) / (S (hcp) +S (fcc) )}×100 measurements are performed in three different non-overlapping measurement fields. In this disclosure, the percentages {S (hcp) / (S (hcp) +S (fcc) )}×100 is the percentage {S (hcp) / (S (hcp) +S (fcc) )}×100.

[0064] As long as the measurement is performed on the same sample, the cut-out location of the cross section of the cemented carbide, the acquisition area of ​​the observation image described in (B2) above, and the measurement field of view are arbitrarily set, and the percentage {S (hcp) / (S (hcp) +S (fcc) It was confirmed that even when measurements of {100} × 100 were performed multiple times, there was almost no variation in the measurement results.

[0065] The cemented carbide of embodiment 1 may include a surface region that is less than 300 μm away from the surface. The percentage {S (hcp) / (S (hcp) +S (fcc) )}×100 is not particularly limited. The reason for this is that the surface region of the cemented carbide is affected by the stress during grinding when the cutting edge of a cutting tool made of the cemented carbide is formed by grinding, and is therefore not an essential part of the cemented carbide that directly affects the life of the cutting tool. On the other hand, the inner region that is 300 μm or more away from the surface of the cemented carbide is less susceptible to stress when the cutting edge of a cutting tool is formed by grinding, and is therefore an essential part of the cemented carbide that affects the life of the cutting tool. Therefore, in the cemented carbide of the present disclosure, the percentage {S (hcp) / (S (hcp) +S (fcc) )}×100. The percentage {S (hcp) / (S (hcp) +S (fcc))}×100 may be, for example, less than 45%.

[0066] <Method of manufacturing cemented carbide> The cemented carbide of the embodiment 1 can be manufactured by carrying out the steps of preparing raw material powder, mixing, molding, and sintering in the above-mentioned order. Each step will be described below.

[0067] <Preparation process> The preparation step is a step of preparing a raw material powder of the cemented carbide. Examples of the raw material powder include tungsten carbide powder (hereinafter also referred to as "WC powder"), cobalt (Co) powder, a first element powder, and an alloy powder of the first element and cobalt. Examples of the first element powder include silicon (Si) powder, phosphorus (P) powder, germanium (Ge) powder, tin (Sn) powder, rhenium (Re) powder, ruthenium (Ru) powder, osmium (Os) powder, iridium (Ir) powder, and platinum (Pt) powder. Examples of the raw material powder include nickel (Ni) powder, niobium carbide (NbC) powder, carbide (Cb) powder, and carbide (Cc) powder. tantalum (TaC) powder, titanium carbonitride (TiCN) powder, chromium carbide (Cr3C2) powder, etc. can be prepared. These raw material powders can be commercially available. The average particle size of these raw material powders is not particularly limited and can be, for example, 0.5 to 2 μm. The average particle size of the raw material powder means the average particle size measured by the FSSS (Fisher Sub-Sieve Sizer) method. The average particle size is measured using a "Sub-Sieve Sizer Model 95" (trademark) manufactured by Fisher Scientific.

[0068] <Mixing process> The mixing step is a step of mixing the raw material powders prepared in the preparation step in a predetermined ratio. A mixed powder in which the raw material powders are mixed is obtained by the mixing step. The mixing ratio of the raw material powders is appropriately adjusted depending on the composition of the target cemented carbide.

[0069] The raw material powders can be mixed by a conventionally known mixing method such as an attritor, a ball mill, or a bead mill. Conventional known conditions can also be used for the mixing conditions. The mixing time can be, for example, 2 hours or more and 20 hours or less.

[0070] After the mixing step, the mixed powder may be granulated as necessary. By granulating the mixed powder, it becomes easier to fill the mixed powder into a die or a mold during the molding step described below. For granulation, a known granulation method can be applied, and for example, a commercially available granulator such as a spray dryer can be used.

[0071] <Forming process> The molding step is a step of molding the mixed powder obtained in the mixing step into a shape for a cutting tool to obtain a molded body. The molding method and molding conditions in the molding step are not particularly limited and may be general methods and conditions.

[0072] <Sintering process> The sintering step is a step of sintering the compact obtained in the compacting step to obtain a cemented carbide intermediate body. Specifically, the compact is held under conditions of 7 MPa and 1360°C for 2 hours.

[0073] <Cooling process> The cooling step is a step of cooling the cemented carbide intermediate body after the sintering step. Specifically, the cemented carbide intermediate body is cooled to 1200°C in a vacuum and held for 30 minutes. Then, the cemented carbide intermediate body is slowly cooled to 1000°C in a vacuum at a temperature drop rate of -0.5°C / min. Then, the cemented carbide intermediate body is rapidly cooled to room temperature (23°C) in a vacuum at a temperature drop rate of -20°C / min to obtain the cemented carbide of the first embodiment.

[0074] <Features of the method for producing the cemented carbide according to the first embodiment> In the method for producing a cemented carbide according to the first embodiment, the sintering step is performed by holding the cemented carbide intermediate body under conditions of 7 MPa and 1360°C for 2 hours. In the cooling step, the cemented carbide intermediate body is cooled to 1200°C in a vacuum and held for 30 minutes, then the cemented carbide intermediate body is slowly cooled to 1000°C in a vacuum at a temperature drop rate of -0.5°C / min, and then the cemented carbide intermediate body is quenched to room temperature (23°C) in a vacuum at a temperature drop rate of -20°C / min. Under these conditions, the percentage {S (hcp) / (S (hcp) +S (fcc) )}×100 is 45% or more. The present inventors have found, as a result of extensive investigations, that the cemented carbide of the present disclosure can be realized by employing such a sintering step and a cooling step.

[0075] [Embodiment 2: Cutting tool] A cutting tool according to one embodiment of the present disclosure (hereinafter also referred to as "embodiment 2") includes a cutting edge made of the cemented carbide of embodiment 1. In this disclosure, the cutting edge refers to a portion involved in cutting. More specifically, the cutting edge refers to a region surrounded by a cutting edge ridge and an imaginary surface that is 0.5 mm or 2 mm away from the cutting edge ridge toward the cemented carbide side.

[0076] Examples of cutting tools include cutting tools, drills, end mills, indexable cutting tips for milling, indexable cutting tips for turning, metal saws, gear cutting tools, reamers, taps, etc. As shown in Fig. 2, the cutting tool 10 of the second embodiment can exhibit excellent effects, particularly in the case of an end mill. The cutting edge 11 of the cutting tool 10 shown in Fig. 2 is made of the cemented carbide of the first embodiment.

[0077] In the cutting tool of the second embodiment, the cemented carbide of the first embodiment may constitute the whole of these tools or may constitute a part of them. Here, "constitute a part" refers to a mode in which the cemented carbide of the first embodiment is brazed to a predetermined position of any substrate to form a cutting edge.

[0078] The cutting tool of the second embodiment may further include a hard film that covers at least a part of the surface of the substrate made of cemented carbide. The hard film may be made of, for example, diamond-like carbon or diamond.

[0079] The cutting tool of the second embodiment can be obtained by forming the cemented carbide of the first embodiment into a desired shape. EXAMPLES

[0080] The present embodiment will be described in more detail with reference to examples, although the present embodiment is not limited to these examples.

[0081] [Preparation of cemented carbide] Each sample of cemented carbide was prepared according to the following procedure. <Preparation process> As the raw material powders, WC powder (average particle size: 1 μm), Co powder (average particle size: 1 μm), first element powder, TiCN powder (average particle size: 1 μm), Cr3C2 powder (average particle size: 1 μm), Ni powder (average particle size: 1 μm) were prepared. As the first element powders, silicon (Si) powder (average particle size: 1 μm), phosphorus (P) powder (average particle size: 1 μm), germanium (Ge) powder (average particle size: 1 μm), tin (Sn) powder (average particle size: 1 μm), rhenium (Re) powder (average particle size: 1 μm), ruthenium (Ru) powder (average particle size: 1 μm), osmium (Os) powder (average particle size: 1 μm), iridium (Ir) powder (average particle size: 1 μm), and platinum (Pt) powder (average particle size: 1 μm) were prepared.

[0082] <Mixing process> A mixed powder was obtained by mixing the raw material powders for 10 hours using an attritor in the ratios shown in Table 1. The ratio (mass%) of each raw material powder shown in Table 1 is the ratio when the entire mixed powder is taken as 100 mass%.

[0083] [Table 1]

[0084] <Forming process> The mixed powder was pressed to obtain a rod-shaped compact.

[0085] <Sintering process> The compact was held at the pressure shown in the "Holding pressure" column and at the temperature shown in the "Holding temperature" column for the time shown in the "Holding time" column in the "Sintering step" column of Table 2. In this way, a cemented carbide intermediate was obtained.

[0086] <Cooling process> For Samples 1 to 16 and Samples 101 to 105, the cemented carbide intermediates after the sintering step were cooled in a vacuum to 1200°C (described in the "First cooling temperature" column of Table 2) and held for 30 minutes (described in the "First holding time" column of Table 2). Then, the cemented carbide intermediates were slowly cooled in a vacuum to 1000°C at a temperature drop rate of -0.5°C / min (described in the "Temperature drop rate to 1000°C" column of Table 2). Then, the cemented carbide intermediates were quenched in a vacuum to room temperature (23°C) at a temperature drop rate of -20°C / min (described in the "Temperature drop rate to 23°C" column of Table 2) to obtain the cemented carbide of each sample.

[0087] For Sample 106 and Sample 107, the cemented carbide intermediate body after the sintering step was quenched in a vacuum to room temperature (23°C) at a temperature drop rate of -20°C / min (shown in the "Cooling rate down to 23°C" column in Table 2) to obtain each cemented carbide sample.

[0088] [Table 2]

[0089] [Evaluation of cemented carbide] <Content (volume %) of tungsten carbide particles and binder phase (volume %) of cemented carbide> The content (volume %) of tungsten carbide particles and the content (volume %) of the binder phase of the cemented carbide of each sample were measured. The specific measurement method is as described in embodiment 1. The results are shown in the "WC particle content" and "binder phase content" columns of "Cemented carbide" in Table 3. Furthermore, the total content of tungsten carbide particles and the binder phase of the cemented carbide are shown in the "WC particle + binder phase content" column of "Cemented carbide" in Table 3. In Table 3, it was confirmed that the cemented carbide with the "WC particle + binder phase content" column of less than 100 volume % further contained TiCN or Cr3C2.

[0090] [Table 3]

[0091] <Cobalt content in binder phase> The cobalt content of the binder phase of each sample of cemented carbide was measured. The specific measurement method is as described in embodiment 1. The results are shown in the "Co content" column of "Binder phase" in Table 4.

[0092] <Type of the first element, and {M1 / (M1+M2)}×100> In the binder phase of the cemented carbide of each sample, the type of the first element and the percentage {M1 / (M1+M2)}×100 of the mass M1 of the first element relative to the sum M1+M2 of the mass M1 of the first element and the mass M2 of cobalt were measured. The specific measurement method is as described in embodiment 1. The results are shown in the "First element" and "{M1 / (M1+M2)}×100" columns of "Binder phase" in Table 4. The samples marked with "-" in the "First element" column do not contain the first element.

[0093] <{S (hcp) / (S (hcp) +S (fcc) )}×100> The area S of cobalt having the hcp structure in the internal binder phase of each sample of cemented carbide at a distance of 300 μm or more from the surface (hcp) and the area S of cobalt with fcc structure (fcc) The total area S (hcp)Percentage of {S (hcp) / (S (hcp) +S (fcc) )}×100 was measured. The specific measurement method is as described in the first embodiment. The results are shown in Table 4 under "bonded phase" as "{S (hcp) / (S (hcp) +S (fcc) )}×100" column.

[0094] [Cutting test] A round bar made of cemented carbide of each sample was machined to prepare a radius end mill with a blade diameter of φ6 mm. The radius end mill was used to perform intermittent side cutting of Inconel 718 aged material (with φ2 mm holes at equal intervals). The cutting conditions were cutting speed Vc 30 m / min, feed per blade fz 0.1 mm / blade, cutting depth (axial direction) ap 3.0 mm, cutting depth (radial direction) ae 1.0 mm, wet. The cutting length until chipping of the cutting edge occurred was measured. The longer the cutting length, the longer the tool life. The results are shown in the "Cutting length" column of "Cutting test" in Table 4. The above processing conditions correspond to intermittent cutting of high-strength materials.

[0095] [Table 4]

[0096] [Consideration] The cemented carbide and cutting tools of Samples 1 to 16 correspond to Examples. The cemented carbide and cutting tools of Samples 101 to 107 correspond to Comparative Examples. It was confirmed that the cutting tools of Samples 1 to 16 had longer tool life than the cutting tools of Samples 101 to 107.

[0097] Although the embodiments and examples of the present disclosure have been described above, it is intended from the outset that the configurations of the above-described embodiments and examples may be appropriately combined or modified in various ways. The embodiments and examples disclosed herein are illustrative in all respects and should not be considered as limiting. The scope of the present invention is indicated by the claims, not by the embodiments and examples described above, and is intended to include the meaning equivalent to the claims and all modifications within the scope. [Explanation of symbols]

[0098] 1 Tungsten carbide particles, 2 binder phase, 3 cemented carbide, 10 cutting tool, 11 cutting edge.

Claims

1. A cemented carbide comprising a plurality of tungsten carbide particles and a binder phase, The cemented carbide contains 89 volume % or more of the tungsten carbide particles and the binder phase in total, The cemented carbide contains 1.8% by volume or more and 20% by volume or less of the binder phase, The binder phase contains 80% by mass or more of cobalt, The cemented carbide includes an internal region having a distance from the surface of 300 μm or more; In the binder phase of the internal region, the area S of cobalt having a hcp structure (hcp) and the area S of cobalt having an fcc structure (fcc) The area S (hcp) Percentage of {S (hcp) / (S (hcp) +S (fcc) )} × 100 is 45% or more, the binder phase further comprises at least one first element selected from the group consisting of silicon, phosphorus, germanium, tin, rhenium, ruthenium, osmium, iridium, and platinum; A cemented carbide, wherein in the binder phase, a percentage of the mass M1 of the first element relative to a sum M1+M2 of the mass M1 of the first element and the mass M2 of cobalt, {M1 / (M1+M2)}×100, is 1% or more and 6.2% or less.

2. The percentage {S (hcp) / (S (hcp) +S (fcc) 2. The cemented carbide according to claim 1, wherein x 100 is 50% or more and 70% or less.

3. A cutting tool having a cutting edge made of the cemented carbide according to claim 1 or 2.

Citation Information

Patent Citations

  • Cutting tool having excellent deposition chipping resistance

    JP2019063932A

  • Surface-coated cutting tool excellent in deposition chipping resistance

    JP2019063937A

  • Cutting tools

    JP2020504780A

  • Hyperfine-grained cemented carbide

    JP2004131769A